Projeto com Atividades Didáticas Integradas (ADIs): uma proposta para o ensino de língua portuguesa - COELHO, Rosiane Maria da Silva (Universidade Federal do Oeste do Pará, 2021)
The need to train subjects who make use of the Portuguese language in a reflexive, creative, critical and conscious way, be it in the oral modality or in the writing is not only fundamental. It is, above all, urgent. We need to increase students' knowledge about the language with which they communicate with each other, so that they can act with criticality in the most diverse interactive situations and in different social spaces. Therefore, Portuguese language teaching should not be limited to formal prescriptivism, in which the text is used solely and exclusively to analyze linguistic elements, because by acting according to this conception of teaching, we will be canceling the possibilities, above of everything, to form subject-citizens. In addition, the present study has the main objective of analyzing the extent to which teaching from the use of discursive genres through an organized project with Integrated Didactic Activities (ADIs) of reading, orality, writing and linguistic reflection collaborate to extend the learners on the language (act). The study was developed with students of a project of acceleration paraense denominated MUNDIAR (Elementary School), in a state public school, in the city of Santarém. The methodology used was research - participatory, in which there is the possibility of reflection on the practice itself in the classroom in order to reconstruct it. The research is based on the theoretical postulates of BAKHTIN (2014, 2016,2017) and on studies of researchers such as MARCUSHI, KLEIMAN, ROJO, ANTUNES, GERALDI (1997, 2003, 2012), MOURA (2017) among others who consider language (act) as social, historical and cognitive activity. From the analysis of the data, the importance of the discursive genre as an object of teaching was verified, as well as the pedagogical mediation with a project organized with the use of Integrated Didactic Activities, because from the proposed activities, the students constructed new knowledge in orality, reading, written production and linguistic analysis, because they participated in interactive situations of real use of the language.